A Review of Analytical Methods for the determination of Clopidogrel in Pharmaceuticals and Biological Matrices. (4th March 2018) - J., Kavitha; K. S., Kokilambigai; R., Seetharaman; R. R., Harini; Kaaviya, A. A.; P., Sowndaravel; K. S., Lakshmi
ABSTRACT: P2Y12 belongs to a group of G protein-coupled (GPCR) purinergic receptors and is a receptor for adenosine diphosphate (ADP). The P2Y12 receptor is involved in platelet aggregation and acts as a biological target for treating thromboembolisms and other clotting disorders. The use of Clopidogrel (CLO) has improved the morbidity and mortality endpoints including cardiovascular death, recurrent myocardial infarction (MI) and stroke at 30 days after percutaneous coronary intervention (PCI). CLO is one such drug that specifically and irreversibly inhibits the P2Y12 subtype of ADP receptor. This review delivers a detail description of various analytical methods published for the estimation of CLO and its combinations in pharmaceuticals and biological matrices. The review highlights the basic as well as advanced techniques performed for estimating CLO. The most commonly used assay techniques were UV and Visible spectrophotometry, high performance liquid chromatography (HPLC), high performance thin layer chromatography (HPTLC), micellar liquid chromatography (MLC), micellar electro kinetic chromatography (MEKC) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Despite other analytical methods employed for the assay of CLO, the review reveals that the technique of HPLC with UV detection was widely used.